Pension systems, ageing and the stability and growth pact - Beetsma, Roel M. W. J.; Oksanen, Heikki; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2007)
This paper explores how the Stability and Growth Pact may cope with the future costs of population ageing in the European Union. Clearly, population ageing has forced countries to reform their pension systems, and will continue to do so, both by reducing the generosity of pension arrangements and by switching to funding rather than relying on pure pay-as-you go pension provision. We study how such reforms affect the room for adhering to the Pact, but also how the Pact may induce or hamper the incentives for reform. In our analysis we will draw on recent literature on the Pact and on the pensions and the ageing problem. We will also calibrate a simple model for addressing intergenerational equity.
Economic Papers